Sport type determines differences in executive functions in elite athletes. (September 2018) - Krenn, Bjoern; Finkenzeller, Thomas; Würth, Sabine; Amesberger, Günter
Abstract: Objectives: Past research has indicated the significance of Executive Functions (EF) in several sports. According to the cognitive skill transfer hypothesis, training in specific cognitive tasks may have beneficial effects on related but untrained tasks. Considering the differing cognitive demands of several sports, differences in EF between sport types were addressed. Design: EF performances of elite athletes in static, interceptive, and strategic sports were compared using a cross sectional study design. Method: Austrian elite athletes ( N  = 184; 110 male/64 female; mean age 23.21 ± 4.48 years) of various sports conducted three tests at the starting point of their sport-psychological consultancy, measuring inhibition and interference control (flanker task), cognitive shifting (adopted flanker task including a second task to shift response reactions) and working memory (2-back task). Results: MANOVAs for each test indicated differences between sport types: Strategic sports revealed benefits in comparison to static sports in mean reaction times, cognitive shifting and to a certain extent working memory. Discriminant analysis clarified a significant differentiation between these three sport types considering the main scores of all three tests as independent variables. Conclusions: The results emphasize the role of EF in high-performance sports and demonstrate that athletes differ in EF according to their individual sports. This finding suggests that the development of EF might be favored by the deliberate practice of strategic sports, and/or that EF might play a more prominent role in strategic sports. Highlights: Differences in Executive Functions (EF) between sport types were detected. 184 elite athletes of various sports conducted three tests measuring core EF. Athletes of strategic sports showed benefits on inhibition and shifting. Athletes of static sports showed worse EF performances.